Knowledge Towards Artificial Intelligence among Physical Therapists Working in Pakistan: Knowledge of AI Among Physical Therapists - Afzal, Mamoona Tasleem; Mehreen, Fatima; Ali, Nahid; Aftab, Rozina; Habib, Iqra; Ahmed, Muhammad Rauf (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
AI is a software system that simulates human intelligence in performing tasks and actions. In modern healthcare system, key aspects of AI include diagnosis, treatment, and prevention of disease. Objective: To determine the knowledge about AI among physical therapists working in Pakistan and to find out level of agreement related to advantages of AI, regarding use of AI in Rehabilitation and impact of AI on future of Rehabilitation. Methods: The study used convenience sampling in Pakistani hospitals and clinics, collecting data from 305 physiotherapists via hospital visits and an online questionnaire. Analysis was done using SPSS 23. Results: Out of 305 participants, 120 were males and 185 were females. 116 were employed in public sector and 186 were employed in private sector. The frequency of physiotherapists who are familiar with AI came out to be 92.5%. About 56.4% physical therapist agreed about uses of AI in rehabilitation. 55.1% physical therapist believed that there are advantages of AI in rehabilitation and there will be a positive impact of AI on rehab in future according to 53.8% of physical therapist. Conclusions: The findings suggest that high frequency of knowledge of AI among physical therapist working in Pakistan. Many physical therapists believed that AI has the positive impact on rehabilitation.